PERAWATAN MESIN SUCKER MULLER DI PT. DLH - Darsini Darsini; Bayu Prabowo (Politeknik Negeri Ketapang, 2021)
PT. DLH Sukoharjo is a textile industry which is engaged in weaving. Observations were made on the Sucker Muller machine which often experienced jams on the cilynder drier, fan, beam stand and bearings and when the beam rotated it could not maximize production results. especially in the Weaving I section in the Sizing section. The problem that often occurs is the inefficient way of maintaining the sizing machine by the factory, which causes delays in the amount of production. In solving the problem, it is done by treating the muller sucker machine. The preventive maintenance method used for maintenance and repair as well as damage prevention. Based on the analysis, it was found that the Mean Time To Failure (M'I'I'F) of the Sucker Muller engine components was 6.63 hours and the Mean Time To Repair (MTTR) value was 573,531 hours.